Stress relief: emerging methods to mitigate dissociation-induced artefacts. Issue 11 (November 2021) - Machado, Léo; Relaix, Frederic; Mourikis, Philippos
Abstract : The rapid progress of single-cell RNA-sequencing (scRNA-seq) at large scales has led to what seemed impossible until recently: the generation of comprehensive transcriptional maps of nearly all cells in multicellular tissues. We pinpoint three key elements as being critical to the production of these maps: scalability, spatial information, and accuracy of the transcriptome of the individual cells. Here, we discuss the ramifications of traditional cell-isolation protocols when capturing the transcriptional signature of cells as they exist in their native tissue context, the methods that have been developed to avoid these distortions, and the biological processes that have unraveled on account of these upgraded methodological approaches. Highlights: Accuracy of single-cell transcriptomes is a key challenge for the construction of second-generation atlases. Standard cell dissociation methods induce strong transcriptional modifications in the majority of cell types. The main determinant of these changes is dissociation time, not cell type or tissue of origin. As a consequence, a large number of published single-cell atlases across tissues and biological set-ups are contaminated by cell dissociation-induced artefacts. A number of methods have been developed that moderate the dissociation-induced artefacts. Implementing (and optimizing) these methods widely will have a major impact towards a more accurate representation of cell states as they exist in their native tissue context.